Familial Dysautonomia (FD) Human Embryonic Stem Cell Derived PNS Neurons Reveal that Synaptic Vesicular and Neuronal Transport Genes Are Directly or Indirectly Affected by IKBKAP Downregulation. - Sharon Lefler; Malkiel A Cohen; Gal Kantor; David Cheishvili; Aviel Even; Anastasya Birger; Tikva Turetsky; Yaniv Gil; Sharona Even-Ram; Einat Aizenman; Nibal Bashir; Channa Maayan; et al. (PLoS ONE, 2015)
A splicing mutation in the IKBKAP gene causes Familial Dysautonomia (FD), affecting the IKAP protein expression levels and proper development and function of the peripheral nervous system (PNS). Here we found new molecular insights for the IKAP role and the impact of the FD mutation in the human PNS lineage by using a novel and unique human embryonic stem cell (hESC) line homozygous to the FD mutation originated by pre implantation genetic diagnosis (PGD) analysis. We found that IKBKAP downregulation during PNS differentiation affects normal migration in FD-hESC derived neural crest cells (NCC) while at later stages the PNS neurons show reduced intracellular colocalization between vesicular proteins and IKAP. Comparative wide transcriptome analysis of FD and WT hESC-derived neurons together with the analysis of human brains from FD and WT 12 weeks old embryos and experimental validation of the results confirmed that synaptic vesicular and neuronal transport genes are directly or indirectly affected by IKBKAP downregulation in FD neurons. Moreover we show that kinetin (a drug that corrects IKBKAP alternative splicing) promotes the recovery of IKAP expression and these IKAP functional associated genes identified in the study. Altogether, these results support the view that IKAP might be a vesicular like protein that might be involved in neuronal transport in hESC derived PNS neurons. This function seems to be mostly affected in FD-hESC derived PNS neurons probably reflecting some PNS neuronal dysfunction observed in FD.